Effects of high-intensity pulsed ion beam irradiation on the structural thermal stability of Fe80Si7.43B12.57 metallic glass - Zhang Qi; Mei Xianxiu; Guan Tong; Zhang Xiaonan; Remnev G. E. Gennady Efimovich; Pavlov S. K. Sergey Konstantinovich; Wang Younian (2019, 2019)
Title screen